Spotlight on borderline-IGHV mutational status in chronic lymphocytic leukemia - Rammal, Souraya; Semaan, Warde; Aprahamian, Natalia; Moussallem, Romy; Chebly, Alain (Frontiers in Oncology, 2024)
Mutated or unmutated immunoglobulin heavy chain (IGHV) gene is an important prognostic factor in chronic lymphocytic leukemia (CLL). However, a small fraction of patients with CLL are classified as borderline (BL)-IGHV. Few data are available on this subgroup of CLL. In this paper, we retrospectively report and analyze data from 21 patients with BL-IGHV CLL, showing the heterogeneity of this subgroup of CLL and paving the way for more research focusing on this entity to optimize the management and treatment of patients with Borderline-IGHV CLL.